Meningkatkan Akurasi Perkiraan Waktu Proyek Perangkat Lunak Dalam COCOMO II Dengan Mengubah Nilai Parameter - Putri, Rahmi Rizkiana; Rahmawati, Weny Mistarika (INTEGER: Journal of Information Technology, 2019)
Good management of software projects can be obtained through accurate time estimates. When estimating less accurate time it will affect the lack of effective management of the software project and the entire process during project development. Barry Boehm, an inventor of COCOMO, has developed the COCOMO 1 cost driver that has an effect on the accuracy of the estimated time results. But if you only use the COCOMO II cost driver, it is still far from the accuracy of the desired results. Therefore it is necessary to change the values of parameters C and D for estimated time. Changes in parameter values are done by decreasing the initial gradation by 0,1 so that the approximate results become more optimal and close to the original values. Based on the implementation of the proposed method, the results show that the error decreases to% when compared to using only the COCOMO I and COCOMO II cost drivers without changing parameter values. So that the accuracy of the estimated project time can increase.